2015
DOI: 10.1016/j.jstrokecerebrovasdis.2014.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Can Trained Field Community Workers Identify Stroke Using a Stroke Symptom Questionnaire as well as Neurologists?

Abstract: Background Stroke is a leading cause of morbidity and mortality worldwide. There is a paucity of data from South Asia where stroke is highly prevalent. Validated tools administrable by Community Health Workers (CHWs) are required to identify stroke in the community in a resource strapped region such as this. Methods The study was conducted in a transitional slum in Karachi, Pakistan. Questionnaire for Verifying Stroke-Free Status (QVSFS) was adapted and translated into Urdu. Two CHWs, trained by a neurologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“… 64 65 While most studies that involve CHWs include a component of training, none of them report the content, length or effectiveness of training on CHWs. Studies from South Africa, 66 67 Pakistan, 68 India, 69–71 China, 72 Dominican Republic, 73 Guatemala, 74 Thailand, 75 Mexico 76 and the Mexican–USA border 77 have shown innovative ways of involving CHWs for the prevention and control of CVD and its risk factors. However, these studies did not measure the impact of training on CHW knowledge and skill set.…”
Section: Discussionmentioning
confidence: 99%
“… 64 65 While most studies that involve CHWs include a component of training, none of them report the content, length or effectiveness of training on CHWs. Studies from South Africa, 66 67 Pakistan, 68 India, 69–71 China, 72 Dominican Republic, 73 Guatemala, 74 Thailand, 75 Mexico 76 and the Mexican–USA border 77 have shown innovative ways of involving CHWs for the prevention and control of CVD and its risk factors. However, these studies did not measure the impact of training on CHW knowledge and skill set.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al has recently reported on a translation of the 8-item QVSFS into Urdu with the administration of the questionnaire among 322 community-dwelling Pakistani subjects using ecologically valid pictures and found a sensitivity, specificity and NPV for detection of stroke of 71%, 85.8% and 95% respectively. However in that study comparison of the questionnaire with and without the pictogram was not reported (13). In this study, pictograms were in line diagrams with a strong agreement between the two versions of the questionnaire.…”
Section: Discussionmentioning
confidence: 94%
“…The QVSFS(26) was intended to verify the stroke-free status and Stroke impact scale to assess the post-stroke quality of life. NIMHANS Headache questionnaire(27) was used for headaches and EAR3Q(28) for bowel diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Four tools - MDRF-IDRS[21], Simple DRS[22], DRS-urban Indians[23], IDRS[24] were for risk scoring of diabetes which had showed moderate sensitivity and specificity. The QVSFS[25]was intended to verify the stroke-free status, NIMHANS Headache questionnaire[26] for headache and EAR3Q[27] for bowel disease, all these tools had high sensitivity and NPV. The EPOCH-2[28] and MNA[29] were assessed cardio-vascular and nutritional status respectively and reported moderate reliability for both.…”
Section: Resultsmentioning
confidence: 99%